2020
DOI: 10.21597/jist.684130
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Polydopamine-dip Coating as a Gentle Surface Modification Process for Cryogel Disks

Abstract: The process called "polydopamine-dip coating" was successfully applied to modify the surface of poly(2-hydroxyethyl methacrylate), PHEMA, cryogel disks for the first time. This facile surface modification process fitted very well to the chemistry of cryogels since the integrity of the cryogel disks was maintained during the whole process. Polydopamine (PDA) nanocoating process was observed to be homogeneously performed through the pores and there was a net color change from white to brown after 24 h. The obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For 3D printed PEEK scaffolds, the ideal coating can also be constructed by impregnation using PDA. Ma et al [18] implanted extracellular vesicles on a 3D-printed PEEK scaffold fixed with polydopamine into New Zealand white rabbits, and showed that this scaffold showed excellent osteogenic ability after 6 and 12 weeks through in vivo imaging, microCT, histology and immunohistochemical analysis. The cell adhesion sequence of arginine-glycine-aspartate (Arg−Gly−Asp, RGD) found in fibulin can bind to integrin receptors to mediate cell adhesion [19] .…”
Section: Fixation Of Bioactive Substancementioning
confidence: 99%
“…For 3D printed PEEK scaffolds, the ideal coating can also be constructed by impregnation using PDA. Ma et al [18] implanted extracellular vesicles on a 3D-printed PEEK scaffold fixed with polydopamine into New Zealand white rabbits, and showed that this scaffold showed excellent osteogenic ability after 6 and 12 weeks through in vivo imaging, microCT, histology and immunohistochemical analysis. The cell adhesion sequence of arginine-glycine-aspartate (Arg−Gly−Asp, RGD) found in fibulin can bind to integrin receptors to mediate cell adhesion [19] .…”
Section: Fixation Of Bioactive Substancementioning
confidence: 99%
“…Despite numerous studies focusing on the adsorptive properties of PD coated surfaces [13,[17][18][19][20][21][22], there is little or no comprehensive information about the kinetics of metal adsorption on porous polymers coated with mussel-inspired chemistry. However, adsorption kinetics are important in the design and control of the entire adsorption process [23,24].…”
Section: Introductionmentioning
confidence: 99%